The Social Cost of Mental Health - Marinković, Lada S.; Marinković, Dušan S. (Sociološki pregled, 2019)
This paper deals with the analysis of mental health as kind of social capital, which, as a resource, has its own social and economic value. The paper discusses the most important contributions to the research into mental health from a sociological perspective with the aim of arguing that this topic is highly relevant for sociology. The authors particularly focus on reconsidering the policy related to mental health that has been developed in the field of biopolitics of the new biological order and profiled as “psychopolitics“, without which the modern concept of mental health care cannot be understood. Relevant data on the global epidemic situation are discussed in the paper and it is argued that mental disorders are not restricted to limited groups of predisposed individuals, but that it rather represents the main problem of public health with profound consequences for the whole society. Keywords: mental health, social capital, sociology, bio(psycho)politics, mental illness.